SISTEM INFORMASI ADOPSI HEWAN PADA MEDAN ANIMAL RESCUE BERBASIS WEB - Khory, Dario; Linardi, Winnie Quinn; Veronica, Kherin; Gohzali, Hernawati; Halim, Arwin (Majalah Ilmiah METHODA, 2024)
The welfare of adopted animals is an important aspect that should be a concern for improving the quality of life and overall health of these animals. However, in the real situation that occurs, the welfare of adopted animals is often neglected by those who adopt these animals. Proper welfare practices for pets can enhance the quality of life and ensure their good health, reducing the risk of diseases and preventing disease transmission. Medan Animal Rescue is an organization dedicated to the rescue and placement of adopted animals. To support  the process of animal rescue and placement, an information system is needed to facilitate the activities at Medan Animal Rescue. The information system is developed using the waterfall methodology and tested using the black box testing method and user acceptance testing (UAT). The ultimate result of this research is an information system that can be utilized by both Medan Animal Rescue and adopters in the process to enhance the welfare of adopted animals.